GIS mapping in the geodemographic studies (Case study of the Republic of Belarus) - Antipova, Ekaterina; Fakeyeva, Liudmila; Karobkin, Aliaksandr (Hungarian Geographical Bulletin, 2012)
The work deals with the options of using geoinformational technologies in the population geography as exemplified by the GIS-models of the rural population of the Republic of Belarus (RB). The methods to create GIS-model with a brief characteristic of the stages are presented. The comparative analysis of two methods of mapping of the relative demographic values (colour scales and map-image transformation) is conducted. Technical and practical aspects of the map-image transformation method in geodemography are considered in the first part of the article.Trends of dynamics of rural population size forthe period of 1959–2009 years are detected and characterized in the second part of the article. Spatial patterns were identified in accordance with these trends of the rural population of the RB. The area of RB is typified on the basis of the character of demographic dynamics and natural movement processes of rural population. There have been identified three types of districts by the nature of the dynamics of rural population for the period of 1970–2009 years: stable, growing and shrinking; and three types of natural population movement dynamics for the same period in accordance with spatial and temporal heterogeneity of rural depopulation.